Video Endoscopic Inguinal Lymphadenectomy via 3-Incision Lateral Approach for Vulvar Cancers: Our Preliminary Outcome of 37 Cases. Issue 9 (1st November 2016) - Wu, Qiang; Gong, Zhen; Zhao, Yibing; Sun, Zhihua; Shao, Henghua; Dai, Zhiqin; Qu, Junwei; Xu, Hanzi
Abstract : Objective: The purpose of this study was to build a video endoscopic inguinal lymphadenectomy (VEIL) via the 3-incision superolateral inguinal approach and explore the feasibility and significance of this method for vulvar cancer. Methods: Thirty-seven patients with vulvar cancer who underwent VEIL via the 3-incision superolateral inguinal approach were enrolled and followed up. The number of excised lymph nodes, intraoperative complications, inguinal wound healing, and the prognosis were retrospectively analyzed. Results: The average number of excised lymph nodes per side is 8.8 ± 3.7 (4–18) among the 37 patients and after the new method was more mature, is 9.6 ± 3.6 among the 34 patients treated. Primary healing was found in 36 cases, whereas delayed healing occurred in 1 case complicated with diabetes. The lymph node–positive patients (6 cases) were supplemented with postoperative radiochemotherapy (RCT). All patients survived during the follow-up. Of the 2 recurrent patients, one patient who received surgery again and RCT survived without tumor. The other patient undergoing RCT survived with tumor. Conclusions: Compared with open lymphadenectomy, VEIL via the 3-incision lateral approach provides a feasible, but more cosmetic, and promising minimally invasive modality in clinic for treating patients with vulvar cancer.